2012
DOI: 10.5762/kais.2012.13.3.1153
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Ankle Joint Muscle Strengthening Training and Static Muscle Stretching Training on Stroke Patients' Plantar Pressure and Gait

Abstract: This study was intended to implement ankle joint dorsi flexion training against ankle muscule strength weakening that erodes stroke patients' gait performance to examine the effect of the training on stroke patients' plantar pressure and gait ability. In this study, 36 stroke patients diagnosed with stroke due to cerebral infarction or cerebral hemorrhage were divided to measure 10MWS which are stroke patients' gait variables maximum plantar pressure by area of the sole by collecting data using an F-scan syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 13 publications
1
4
0
Order By: Relevance
“…There was no difference in the maximum pressure between the experimental group and the control group. This is similar to Lee et al (2012), where the preand post ankle muscle strengthening training showed no significant changes in the maximum pressure around the first metatarsal bone area. Furthermore, the average pressure also showed no difference in change for both the experimental and control group.…”
Section: ⅳ Discussionsupporting
confidence: 73%
“…There was no difference in the maximum pressure between the experimental group and the control group. This is similar to Lee et al (2012), where the preand post ankle muscle strengthening training showed no significant changes in the maximum pressure around the first metatarsal bone area. Furthermore, the average pressure also showed no difference in change for both the experimental and control group.…”
Section: ⅳ Discussionsupporting
confidence: 73%
“…Lee et al [15] reported that the time taken in the 10MWT and the TUG was significantly decreased in stroke patients when they underwent plantar flexor stretching for six weeks, perhaps because of an increase in the range of motion in the ankle joints and a decrease in spasticity. In this study, however, the control group undergoing static stretching did not show a significant difference between pre-and post-training in the results of the TUG, the FRT, or the 10MWT.…”
Section: Discussionmentioning
confidence: 99%
“…Kim [14] reported that a short-term application of passive stretching to the plantar flexor of subjects with stroke reduced the excitability of the α-motor neuron and increased the degree of dorsiflexion. Lee et al [15] identified that static stretching of the plantar flexor of stroke patients by using the Q-board for six weeks increased gait velocity in the 10 m walk test (10MWT) and the timed up-and-go test. However, in Bressel and McNair [16]'s research, consistent static stretching of the plantar flexor of stroke patients for 30 minutes reduced the stiffness of the ankle joints for a short period, but gait velocity was not significantly increased in the 10MWT, owing to reduced muscular strength.…”
Section: Introductionmentioning
confidence: 99%
“…Improving the gait is important for the rehabilitation of hemiplegic patients. The foot is very important for a functional gait 5 ) . The foot provides thrust and absorbs the physical impact, and it determines the direction of progress 5 ) .…”
Section: Introductionmentioning
confidence: 99%
“…The foot is very important for a functional gait 5 ) . The foot provides thrust and absorbs the physical impact, and it determines the direction of progress 5 ) . Therefore the ankle joints play an important role in providing thrust during gait and in assisting in maintenance of balance in response to movement of the center of gravity.…”
Section: Introductionmentioning
confidence: 99%